Comparing Tourism Economic Impact by Tourist Arrivals in Heritage Destination: Prambanan-Kalasan Area - Nining Yuniati (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study examines the comparative economic impacts of heritage tourism in the Prambanan and Kalasan areas of Yogyakarta based on tourist arrivals and tourism multiplier effects. The research aims to analyze how differences in tourist expenditure influence direct, indirect, and induced economic impacts within local communities. A quantitative comparative approach was employed using the Keynesian tourism multiplier model. Primary data were collected through surveys and interviews involving tourists, tourism business operators, and tourism workers in both destinations. The analysis focused on tourist expenditure (E), direct income (D), indirect income (N), and induced income (U). The results show that the Keynesian multiplier value in Prambanan reached 6.75, while Kalasan recorded a higher multiplier value of 8.09. Income Multiplier Ratio Type I reached 3.45 in Prambanan and 1.91 in Kalasan, while Income Multiplier Ratio Type II reached 6.39 and 2.73 respectively. Average tourist expenditure per visit in Prambanan was IDR 965,630, significantly higher than Kalasan at IDR 178,370. The findings indicate that Prambanan generated larger aggregate economic impacts, whereas Kalasan demonstrated more efficient local economic circulation with lower leakage levels.